PENGARUH AIRCRAFT IDENTIFICATION (ACID) PESAWAT MILITER TERHADAP KELANCARAN PELAYANAN NAVIGASI PENERBANGAN - Azahra Dian Puspita; Fatmawati; Yuni Saptandari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Aircraft Identification (ACID) has an important role in aviation navigation services. Aircraft Identification is the identity of an aircraft in flight. With Aircraft Identification, the controller can find the flight plan of an aircraft to find out important information from the aircraft such as the origin or destination airport, aircraft type, altitude, route, and others. The problem reviewed in this final project is about the non-uniformity in the shortening of Aircraft Identification of military aircraft in item 7 flight plan. The method of analysis used in this research is descriptive qualitative with data collection methods in the form of observation, interviews, and literature study. The results of this study indicate that there is no uniformity in the abbreviation of Aircraft Identification of military aircraft on item 7 flight plans is included in the category that is very influential because it can hinder the efficiency of developing aviation flight services.